Benefits and challenges of collaborative work in the teaching of Mathematics in the pedagogical residency programBenefícios e desafios do trabalho colaborativo no ensino de Matemática no Programa Residência Pedagógica - Pereira, Irene Castro; da Silva, Paulo Vilhena; Gomes, Cristiane Ruiz (Educação Matemática Pesquisa: Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2021)
Abstract As is pointed out in the literature, collaboration between teachers and other members of the school community not only enhances the teacher's education, but also leads to better student learning. However, it is not always easy to work in partnership, because this requires constant evaluation and the ability to take account of different opinions. For this reason, this study involves an investigation of the benefits and challenges of collaborative work, carried out by the Faculty of Mathematics at the Federal University of Pará, within the scope of the Pedagogical Residency Program, and under the supervision of a preceptor and three residents. Our methodology entailed conducting semi-structured interviews and the results of our analysis showed that the Pedagogical Residency was a means of providing new ideas for the teaching activities of the field schools. It also revealed that the different players involved had difficulty in understanding their roles, when dealing with a new project that is carried out in Brazil. Keywords: Collaborative Work; Teaching of Mathematics; Pedagogical Residency Program Resumo Conforme aponta a literatura, o trabalho colaborativo entre professores e outros membros da comunidade escolar não só enriquecem a formação do professor, como contribuem para um melhor aprendizado por parte dos estudantes. Por outro lado, nem sempre é fácil realizar trabalhos em parceria, porque exigem constante avaliação e a habilidade de lidar com diferentes opiniões. Nesse sentido, no presente trabalho apresentamos uma investigação sobre as contribuições e desafios do trabalho em colaboração, desenvolvido pela faculdade de matemática da Universidade Federal do Pará, no âmbito do programa Residência Pedagógica, na percepção de um preceptor e três residentes. Para tanto, realizamos entrevistas semiestruturadas e nossas análises apontam que o Residência Pedagógica contribui com novas ideias para as atividades docentes da escola campo e revela a dificuldade dos atores em compreenderem seus papéis, tendo em vista tratar-se de um programa novo desenvolvido no Brasil. Palavras-chave: Trabalho Colaborativo; Ensino de Matemática; Programa Residência Pedagógica. Resumen Como se señala en la literatura, la colaboración entre docentes y otros miembros de la comunidad escolar no solo mejora la educación del maestro, sino que también conduce a un mejor aprendizaje de los estudiantes. Sin embargo, no siempre es fácil trabajar colaborativamente, porque requiere una evaluación constante y la capacidad de tener en cuenta las diferentes opiniones. Por tal motivo, este estudio involucra una investigación de los beneficios y desafíos del trabajo colaborativo, realizado por la facultad de matemáticas de la Universidad Federal de Pará, en el ámbito del programa de Residencia Pedagógica, y bajo la supervisión de un preceptor y tres residentes. Nuestra metodología implicó la realización de entrevistas semiestructuradas y los resultados de nuestro análisis mostraron que la residencia pedagógica fue un medio de aportar nuevas ideas para las actividades docentes de las escuelas de campo. También reveló que los diferentes actores involucrados tuvieron dificultad para entender sus roles, considerando que es un nuevo proyecto que se lleva a cabo en Brasil. Palabras clave: Trabajo en colaboración, Enseñanza de matemáticas, Proyecto Residencia Pedagógica